A Novel Prokaryotic Promoter Identified in the Genome of Some Monopartite Begomoviruses - Wang, Wei-Chen; Hsu, Yau-Heiu; Lin, Na-Sheng; Wu, Chia-Ying; Lai, Yi-Chin; Hu, Chung-Chi (PloS one, 2013)
Geminiviruses are known to exhibit both prokaryotic and eukaryotic features in their genomes, with the ability to express their genes and even replicate in bacterial cells. We have demonstrated previously the existence of unit-length single-stranded circular DNAs of Ageratum yellow vein virus (AYVV, a species in the genus Begomovirus, family Geminiviridae) in Escherichia coli cells, which prompted our search for unknown prokaryotic functions in the begomovirus genomes. By using a promoter trapping strategy, we identified a novel prokaryotic promoter, designated AV3 promoter, in nts 762-831 of the AYVV genome. Activity assays revealed that the AV3 promoter is strong, unidirectional, and constitutive, with an endogenous downstream ribosome binding site and a translatable short open reading frame of eight amino acids. Sequence analyses suggested that the AV3 promoter might be a remnant of prokaryotic ancestors that could be related to certain promoters of bacteria from marine or freshwater environments. The discovery of the prokaryotic AV3 promoter provided further evidence for the prokaryotic origin in the evolutionary history of geminiviruses.